Study the Gender’s Role of Khmu in Rearing Large Animals in PhuKhun District, Luang Prabang Province - HUEANGLATSAMY, Phonechan-8899; KEOHAVONG, Bounmy; PHASOUK, Amphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The study aimed to evaluate the influence of gender of Khmu on raising large animals, this study was used 50 questionnaires, the data were analyzed: amount, percentage, mean value and standard deviation of the opinion of the respondents and was used SPSS version 22.0 software to calculate, the results found: The respondents were 58% of male, for the age range between 42 - 49 years was highest at 78%, followed by 50 - 57 years of 10% and lowest <58 years old, 90% was graduated of general education and 10% was completed element school and 98% were farmers and 1 was government staff, the average income from 2-2.5 was highest, followed by 1.3-2 and lowest from 2-3 millions kip/month, 64% of land was purchase by them self, the mean marriage is 16.8 years and there were 4.98 peoples, 3.9 ha and 7.93 head/family, they raised only buffaloes and 74% was purchased by them self. The idea to start raising animals based on decision together and personal factors such as:Income of husband or wife and the education level was not effect on raising animals, which overall has the most influence with = 4.94 and S.D=0.24, for the customs that have been practiced in the past, which holds that male an effluent to decide in the family, it is seen that they do not follow what they used to respect each other, it is seen that they have the most influence with = 4.94 and S.D=0.36), and finally, when they have known about the guidelines, policies, regulations and laws and the promoting equality, which leads to equality in living together. As well as deciding various tasks within the family, which also shows that the activities related to animal husbandry are divided according to the ability and according to the labor that can be done.